Reconstructing the Concept of Women in Islamic and Pesantren Educational Perspectives - Muslih, Mohammad; Syarifah, Syarifah; Ahmadan, Madani (Universitas Negeri Semarang, 2025)
The idea of women in Islam is examined in this article as a key topic in modern Islamic studies, covering theological, sociological, and pedagogical facets. By examining the viewpoints of the Qur'an, Hadith, Islamic academic tradition, and historical precedents, this study seeks to provide a comprehensive picture of women's strategic position and role. This article illustrates how Islam sees women as spiritually equal beings with a variety of roles through scriptural and contextual study. The Qur'an and Hadith's endorsement of men and women's spiritual equality, which dispels patriarchal prejudices, opens the topic. The article then examines the ideas of